Controlled di-lithiation enabled synthesis of phosphine-sulfonamide ligands and implications in ethylene oligomerization - Mote, Nilesh R.; Gaikwad, Shahaji R.; Khopade, V, Kishor; Gonnade, Rajesh G.; Chikkali, Samir H. (Dalton Transactions, 2021)
Catalyst design for ethylene oligomerization has attracted significant interest. Herein, we report the synthesis of phosphine-sulfonamide-derived palladium complexes and examine their performance in ethylene oligomerization. Arresting a dilithiation intermediate of N-(2-bromophenyl)-4-methylbenzenesulfonamide (1) at -84 degrees C selectively produced N-(2-(bis(2-methoxyphenyl)phosphanyl)phenyl)-4-methylbenzenesulfonamide (L1A). However, the same reaction at -41 degrees C delivered a different ligand; 2-(bis(2-methoxyphenyl)phosphanyl)-4-methyl-N-phenylbenzenesulfonamide (L2A). The generality of our strategy has been demonstrated by preparing N-(2-(diphenylphosphanyl)phenyl)-4-methylbenzenesulfonamide (L1B) and 2-(diphenylphosphanyl)-4-methyl-N-phenylbenzenesulfonamide (L2B). Subsequently, L1A and L1B were treated with a palladium precursor to yield 5-membered complexes C1 and C2, respectively. In contrast, L2A upon treatment with palladium produced a 6-membered metal complex C3. Thus, a small library of 7 palladium complexes (C1-C7) were synthesized by varying the donor moiety (pyridine, DMSO, and acetonitrile). The identity of palladium complexes was unambiguously ascertained using a combination of spectroscopic and analytical methods, including single-crystal X-ray diffraction. The performance of the complexes C1-C7 was investigated in ethylene oligomerization and almost all of them were found to be active. The resultant ethylene oligomers were characterized using H-1 and C-13 NMR, MALDI-ToF-MS, and GPC. Detailed screening of reaction parameters revealed 100 degrees C and 40 bars ethylene to be optimal conditions. Complex C5 outperformed other complexes and produced ethylene oligomers with a molecular weight of 1000-1900 g mol(-1).